Pengaturan, Pengelolaan, dan Penggunaan Sarana Prasarana - Karima, Khasna Azizatul; Khasanah, Isrofiah Laela (Innovations in Multidisciplinary Education Journal, 2024)
Efficient management and utilization of infrastructure facilities is essential for the effective implementation of education, so it is necessary to understand this. In the preparation of this article using the literature review method, in which the author collects, analyzes and combines various information from various literature sources that are considered relevant and in accordance with the objectives of the discussion. The definition of arrangement and management is synonymous with the word management which means the process of taking care of and handling something to realize certain goals to be achieved while use means usage or utilization. The purpose of setting and managing good facilities and infrastructure is expected to create a conducive environment that supports the teaching and learning process so that existing infrastructure can be utilized optimally for a long period of time. Methods in sarpras management include: (1) needs analysis and planning, (2) procurement, (3) inventory, (4) distribution and utilization, (5) maintenance, (6) elimination, and (7) supervision and accountability (reporting). In order for the management of sarpras to run optimally, all school members have an obligation to take part in maintaining and caring for existing facilities and infrastructure.